Expert System for Detecting Cat Skin Disease using Certainty Factor Method - Yessi Jusman; Muhammad Ahdan Fawwaz Nurkholid; Amin Musthofa; Wita Yulianti; Farah Ramadhani (Journal of Electrical Technology UMY, 2020)
With the increasing number of people contaminated with cat disease, many veterinarians specializing in cats in Indonesia open up a practice in big cities only. Thus, it is not uncommon for cat owners who are late to provide treatment for skin diseases since the initial symptoms occur. Based on the problems to overcome skin diseases in cats, it is necessary to build a computerized system that has knowledge such as veterinarians and the system can be a tool in diagnosing types of diseases and provide solutions for treatment and prevention with the expert system of Certainty Factor (CF), because the Certainty Factor (CF) method is to prove whether a fact is certain or uncertain in the form of a metric that is usually used in expert systems. The results of the system are to help users, among others, veterinarians in diagnosing skin diseases in cats and animal owners, especially cats to find skin diseases in cats. It is expected to make it easier for doctors and cat owners to determine the type of skin disease based on existing symptoms and get the right treatment method.